Layered O3-NaFe0.5Co0.5O2 as high capacity and low- cost material for sodium ion batteries - Hoang, Nguyen Van; Phuoc, Mai Ngoc; Nguyen, Huynh Le Thanh; Quan, Nguyen Dinh; Man, Tran Van; Phung, Le My Loan (Vietnam Journal of Science and Technology, 2019)
O3-NaFe0.5Co0.5O2 layered cathode material was synthesized by solid state reaction at 900 oC followed by a quenching step in argon atmosphere. The chemical composition and morphology of synthesized material were analyzed by Atomic Absorption Spectroscopy (AAS) and Scanning Electron Microscopy (SEM). The electrochemical properties were evaluated by Cyclic Voltammetry (CV) and charge-discharge cycling. The material NaFe0.5Co0.5O2 shows the sloped discharge curves with high flat voltage plateau and excellent cycling stability. The reversible capacity of about 120 mAh/g at rate C/10 and good capacity retention after 100 cycles were obtained.